Pengaruh Bentuk Latihan Teknik Dengan Metode Circuit Training Terhadap Peningkatan Ketepatan Shooting pada Sekolah Sepak Bola Aseto Tegalrejo - Whily Akhmad Novianto; Agam Akhmad Syaukani; Pungki Indarto (Center for Sports Science , Faculty of Sport Science, Universitas Negeri Padang, 2026)
This study aimed to examine the effect of technical training using the circuit training method on improving shooting accuracy among students of Aseto Tegalrejo Football School. Previous studies have demonstrated the general benefits of circuit training for physical fitness and performance, however, limited research has specifically investigated its integrated application in enhancing technical skills, particularly shooting accuracy, in youth football training contexts. To address this gap, a quasi-experimental design with a two-group pretest–posttest approach was employed. The sample consisted of 30 students divided into an experimental group (n = 15) and a control group (n = 15) selected through purposive sampling. The experimental group received circuit training-based technical exercises, while the control group underwent conventional training. Shooting accuracy was measured using a standardized target-based test. Data were analyzed using paired and independent sample t-tests. The results showed a significant improvement in the experimental group mean score increased from 8.80 to 15.53 (p < 0.001), while the control group showed a smaller improvement 7.67 to 12.13 (p < 0.001). Furthermore, a significant difference was found between groups in posttest results (p < 0.001). These findings indicate that circuit training is more effective in improving shooting accuracy and can serve as an alternative training method in youth football development